Russia's Clashing Ambitions: Arctic Status Quo and World‐Order Revision - Pedersen, Torbjørn; Steinveg, Beate (Politics and Governance, 2024)
Moscow explicitly challenges what it depicts as a Western-led world order amid shifts in the global balance of power. However, while Russia has emerged as a fundamentally revisionist power in the global system, it has sought to maintain the status quo in Arctic regional governance, that is, to preserve the institutions and arrangements that have cemented its status as a great regional power on top of the world. This study, challenging the notions of Arctic exceptionalism and a distinct Arctic regional order, points out an obvious inconsistency in Russia's approach. It argues that Moscow's attempt at dismantling the world order while maintaining the status quo in the Arctic seems bound to fail simply because the current rules-based, liberal international order has also been the order of the Arctic. In conclusion, this study finds that Russia so far has been more successful in diminishing its own Arctic status and isolating itself from formal as well as informal arrangements than revising them.